DEVELOPING A MODEL FOR DYNAMIC DIGITAL TRANSFORMATION CAPABILITIES BASED ON THE TECHNOLOGY-ORGANIZATION-ENVIRONMENT FRAMEWORK TO ENHANCE BANKING PERFORMANCE: INSIGHTS FROM THE INDONESIAN CONTEXT - Abdurrahman
The primary focus of current research is on the application of dynamic capabilities theory (DC) in the study of digital transformation (DT). This is driven by the recognition that DT, as a complex strategic initiative, necessitates various well-structured company capabilities to enhance overall performance. A key challenge in researching DC within the context of DT is defining the necessary capabilities for organizations, taking into account technological, organizational, and environmental aspects (the TOE framework). This is founded on the understanding that DT is a socio-technical initiative that requires integration beyond just technological aspects. Existing literature indicates a limited concentration on integrating DC and the TOE framework, creating an opportunity for research to contribute to the development of company capabilities essential for successful DT management and performance improvement. Thus, this study is crucial in offering diverse perspectives on integrating DC and TOE to formulate dynamic capabilities for digital transformation, particularly within the Indonesian banking industry, currently undergoing DT to meet societal needs and regulatory requirements.